2001
DOI: 10.1007/s004410100362
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic choroidal neurons in the duck eye receive sympathetic input: anatomical evidence for adrenergic modulation of nitrergic functions in the choroid

Abstract: Intrinsic choroidal neurons (ICN) in the duck eye form an intramural ganglionic plexus that may subserve complex integrative functions. A key feature of such ganglia is an innervation by sympathetic postganglionic neurons. The present study was thus aimed at determining the sympathetic postganglionic innervation of ICN. Choroids were processed for double immunofluorescence labelling with the following markers: tyrosine-hydroxylase (TH)/nitric oxide synthase (nNOS), TH/galanin (GAL), dopamine-beta-hydroxylase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…It has been shown that in ducks ICNs are approached by sympathetic nerve fibers; this was confirmed at the ultra-structural level (Schrödl et al 2001b). We postulate that chicken ICNs are also part of the circuit of the sympathetic nervous system as indicated by the presence of TH- and VMAT2-positive boutons in close association.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It has been shown that in ducks ICNs are approached by sympathetic nerve fibers; this was confirmed at the ultra-structural level (Schrödl et al 2001b). We postulate that chicken ICNs are also part of the circuit of the sympathetic nervous system as indicated by the presence of TH- and VMAT2-positive boutons in close association.…”
Section: Discussionmentioning
confidence: 75%
“…Because this antibody did not show positive staining in the chicken choroid (although it did label fibers in prior bird experiments; Schrödl et al 2001b), VMAT2 was used as an alternative marker for catecholamines. Prior to that, the superior cervical ganglion was screened for VMAT2; VMAT2 was detected in numerous neurons and fibers of the respective ganglion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The function of these local networks has been found to depend on the organ. In the gut, the ganglia play a role in the generation and coordination of peristaltic activity and secretion (Furness et al 2004), whereas in the choroid of the eye, they influence blood flow and contraction in the smooth muscle (Schrodl et al 2001(Schrodl et al , 2003. Such peripheral neural networks also receive input from collaterals of extrinsic primary sensory fibres.…”
Section: A Conceptual Structural Modelmentioning
confidence: 98%
“…ICNs may be suitable candidates for the neuronal control of these refractive changes. 12,40,41 Possible targets of ICNs other than those expressing smooth muscle actin are still to be determined.…”
Section: Discussionmentioning
confidence: 99%